Penataan Ruang Situ Tunggilis Untuk Pengembangan Wisata Berbasis Partisipasi Masyarakat Dalam Rangka Peningkatan Kesejahteraan - Janthy T Hidayat; Herman Herman; Dini Valdiani; M. Agus Karmadi; Evyta Wismiana (Rural Development For Economic Resilience (RUDENCE), 2022)
Situ Tunggilis is located in Desa Situsari Village, Kecamatan Cileungsi, is one of the 96 lakes in the Kab. Bogor. Currently, it has not provided benefits for the community even though there are development directions according to the Spatial Plan as desa wisata, this requires optimizing the use of the area. Community service activities aim to develop the site as a tourist attraction in the context of a tourist village and improve the community's ability to manage tourism objects there and to realize the policy of MBKM program. PKM is funded by the MBKM policy research assistance program and community service based on research results and prototypes of the Directorate General of Research, Technology and Higher Education. The implementation method is through field surveys, Focus Group Discussions and training. PKM produces a site development Master Plan with animations and regional icons, HR training, finance and digital marketing. The implications of PKM are having a lake development plan, increasing the ability of the community and BUMDes to manage the lake as a tourist attraction and creating a tourist village and improving community welfare.